2014
DOI: 10.1186/1756-3305-7-243
|View full text |Cite
|
Sign up to set email alerts
|

Estimating trematode prevalence in snail hosts using a single-step duplex PCR: how badly does cercarial shedding underestimate infection rates?

Abstract: BackgroundTrematode communities often consist of different species exploiting the same host population, with two or more trematodes sometimes co-occuring in the same host. A commonly used diagnostic method to detect larval trematode infections in snails has been based on cercarial shedding, though it is often criticized as inaccurate. In the present study we compare infection prevalences determined by cercarial emission with those determined, for the first time, by molecular methods, allowing us to quantify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 62 publications
2
37
0
Order By: Relevance
“…Recent evidence indicates that the routinely used cercarial shedding detection method is greatly outcompeted by molecular detection methods, which identify trematode infection in snails with up to 60.1% higher efficacy. The authors of the study suggested that detection failure is most likely due to the immature and covert infections, which can result in delayed and therefore undetectable (at the time of observation) cercarial shedding [80]. Therefore, the near absence of detected infection in our study may not necessarily be indicative of low snail infection prevalence.…”
Section: Discussionmentioning
confidence: 84%
“…Recent evidence indicates that the routinely used cercarial shedding detection method is greatly outcompeted by molecular detection methods, which identify trematode infection in snails with up to 60.1% higher efficacy. The authors of the study suggested that detection failure is most likely due to the immature and covert infections, which can result in delayed and therefore undetectable (at the time of observation) cercarial shedding [80]. Therefore, the near absence of detected infection in our study may not necessarily be indicative of low snail infection prevalence.…”
Section: Discussionmentioning
confidence: 84%
“…Several pioneering molecular studies have shown that many other species of freshwater snail carry evidence of schistosome infection than traditional methods have inferred previously [75–78]. Another important technical development has been the use of FTA card sampling methods which has enabled convenient storage of schistosome eggs, miracidia and cercariae for more precise genotyping of schistosome populations and species [62, 7981].…”
Section: On Environmental Sampling: Practicalities and Pitfallsmentioning
confidence: 99%
“…elsewhere [18], however, in spite of these disadvantages, the sensitivity and specificity of this diagnostic test, once performed properly, have no equal when compared to other tests.…”
Section: Diagnostics and Treatmentmentioning
confidence: 97%
“…Food-borne trematode zoonoses (FBTZ) start their life cycle as miracidium, a 100-micrometer ciliated developmental stage result of trematodes embryonated eggs, highly mobile in aquatic conditions, upon finding a compatible snail, the miracidium penetrates the tegument of the intermediate host shedding its cilia [17] turning into germinal masses of cells called sporocysts. These sporocysts multiply into several masses of germinal cell each of them originating a redia [18], and these are intermediate germinal stages that develop into cercariae, a highly mobile developmental stage that finally exits the intermediate host by perforation of the snail'st e g ument and then migrates into an aquatic environment, the cercariae, depending on the parasitic trematode species, can penetrate the skin of a second intermediate host and encyst in the muscles of it [19]. Cercariae may also penetrate the skin of the definitive host [6] or lose its tail and become a cyst, an environment-resistant developmental stage on surrounding vegetation or in drinking water.…”
Section: Farm Animals Diseases Recent Omic Trends and New Strategiesmentioning
confidence: 99%